Comparing Three Countries’ Higher Education Students’ Cyber Related Perceptions and Behaviours during COVID-19 - Desireé Cranfield (Electronics, 2021)
In 2020, a global pandemic led to lockdowns, and subsequent social and business restrictions. These required overnight implementation of emergency measures to permit continued functioning of vital industries. Digital technologies and platforms made this switch feasible, but it also introduced several cyber related vulnerabilities, which students might not have known how to mitigate. For this study, the Global Cyber Security Index and the Cyber Risk literacy and education index were used to provide a cyber security context for each country. This research project—an international, cross-university, comparative, quantitative project—aimed to explore the risk attitudes and concerns, as well as protective behaviours adopted by, students at a South African, a Welsh and a Hungarian University, during the pandemic. This study’s findings align with the relative rankings of the Oliver Wyman Risk Literacy and Education Index for the countries in which the universities reside. This study revealed significant differences between the student behaviours of students within these universities. The most important differences were identified between students’ risk attitudes and concerns. It was also discovered that South African students reported having changed their protective online behaviours to the greatest extent, since the pandemic commenced. Recommendations are made suggesting that cyber security training and education, as well as improving the digital trust and confidence in digital platforms, are critical.